Authority control ontologies in the field of linked open data - Serrano-Cobos, Jorge (Anuario ThinkEPI, 2013)
The concept of "big data" is explained as a system of analyzing large amounts of data to discover trends, patterns, correlations and even causality to generate predictions. This discipline can be adapted to the context of the daily work of the information professional dealing with "small data" and web analytics. Examples are provided of tools that support the management and analysis of huge amounts of publicly available data.